Kompetensi Pedagogik Guru Profesional Di Sekolah Dasar Gugus Yudhistira Kecamatan Selogiri Kabupaten Wonogiri - , Haryono; , Prof. Dr. Bambang Sumardjoko; , Dr. Sofyan Anif, M.Si (2017)
This study have three aims to describe: 1) planning of teaching learning activities in classroom, 2) the implementation of the learning process in the classroom, and 3) evaluation of learning outcomes / assessment learning activities conducted by professional teachers in Yudhistira Group of Selogiri Sub District, Wonogiri Regency. This research is qualitative research with etnography design. Data was collected by observation, interview, and documentation. Data analysis use interactive analysis. The validity of the data using source triangulation. Results of this research there are: 1) Planning of learning by professional teacher at Yudhistira Group is done by teacher mastering student characteristics through introduction and observation; Classroom teachers mastered 5 subject areas and sharing with their peer teacher; create lesson plans based on the outline of the lesson plan, but the fact is the preparation of lesson plans just for administrative requirements and just copy and paste from teachers in other schools. 2) The learning process is carried out by a professional teacher of Yudhistira Group requires creativity and patience due to the way teachers teach elementary school children is very different from junior/ high school in terms of treatment. Some teachers in conducting preliminary activities not doing apperception and directly on the core of the learning activities. In addition to the core activities, the teachers also rarely uses the technique of elaboration and confirmation. The potential development of learners is done through extracurricular activities in academic and non academic fields. Communication with students is still one direction where the teacher explains and the students listen, interspersed with question and answer. 3) Evaluation learning of teacher professional is done in groups Yudhistira uses summative assessments conducted by the form daily tests, midterm test and grade promotion test.